2020
DOI: 10.7717/peerj.9369
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of microRNA-mediated interactions in SARS-CoV-2 infection

Abstract: MicroRNAs (miRNAs) are post-transcriptional regulators of gene expression found in more than 200 diverse organisms. Although it is still not fully established if RNA viruses could generate miRNAs, there are examples of miRNA like sequences from RNA viruses with regulatory functions. In the case of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), there are several mechanisms that would make miRNAs impact the virus, like interfering with viral replication, translation and even modulating the host ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
150
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 57 publications
2
150
0
Order By: Relevance
“…In herpesvirus, viral factors block the transcription initiation process by inhibiting TAF4. Targeting transcription process by SARS-CoV-2 could help in preventing the assembling of RNA polymerase II on host genes ( Saçar Demirci and Adan, 2020 ). Genome-wide target predictions have previously shown that TFs are susceptible to regulation by miRNAs ( Enright et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…In herpesvirus, viral factors block the transcription initiation process by inhibiting TAF4. Targeting transcription process by SARS-CoV-2 could help in preventing the assembling of RNA polymerase II on host genes ( Saçar Demirci and Adan, 2020 ). Genome-wide target predictions have previously shown that TFs are susceptible to regulation by miRNAs ( Enright et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human miRs have been associated with a variety of pathophysiological pathways and demonstrate differential expression during viral infections [ 93 , 94 ]. Recently, a few computational studies have shed light on the interplay between human miRs and SARS-CoV-2 target genes, indicating a crucial role in regulating the viral load in host cells [ 95 , 96 ]. However, a comprehensive understanding of the functional role of host miRs during SARS-CoV-2 infection has remained elusive until now.…”
Section: Resultsmentioning
confidence: 99%
“…However, a comprehensive understanding of the functional role of host miRs during SARS-CoV-2 infection has remained elusive until now. Recently, a machine learning-based study predicted that miRs could impact SARS-CoV-2 infection through several mechanisms, such as interfering with replication, translation, and by modulation of the host gene expression [ 95 ]. In this study, we used a computational approach to investigate the potential binding sites of human miRs in the SARS-CoV-2 genome using FIMO [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The izMiR (miRNA prediction software) and PANTHER, bioinformatics based classification systems, identified the possible mature viral and host cell miRNA candidates that could play a crucial role in SARS-CoV-2 infection [59]. According to this study, SARS-CoV-2 genes (Spike, Envelope, Membrane, Nucleocapsid, ORF1ab, ORF3a, ORF6, ORF8, ORF7a, and ORF10) were targeted by multiple human miRNAs ( Figure 3) and these miRNAs already have previously known roles in multiple viral diseases, to illustrate, ORF1ab and ORF3a, two SARS-CoV-2 viral genes, were shown to be targeted by hsa-miRNA 203b-3p which was reported to suppress viral replication in Influenza [60].…”
Section: Article Highlightsmentioning
confidence: 99%